2007
DOI: 10.1111/j.1439-0469.2007.00425.x
|View full text |Cite
|
Sign up to set email alerts
|

The role of character loss in phylogenetic reconstruction as exemplified for the Annelida

Abstract: Annelid relationships are controversial, and molecular and morphological analyses provide incongruent estimates. Character loss is identified as a major confounding factor for phylogenetic analyses based on morphological data. A direct approach and an indirect approach for the identification of character loss are discussed. Character loss can frequently be found within annelids and examples of the loss of typical annelid characters, like chaetae, nuchal organs, coelomic cavities and other features, are given. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
54
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(55 citation statements)
references
References 98 publications
1
54
0
Order By: Relevance
“…Whole body segmentation has been lost, complete with all segmented organ systems, several times within one phylum, namely, the annelids. (41,42) Two unsegmented groups, the sipunculids and the echiurans, previously regarded as phylum level taxa, have now been shown to be nested within polychaete annelids. (43) Both taxa retain transient vestiges of a segmented body plan during their development.…”
Section: The Case Against a Common Origin Of Segmentationmentioning
confidence: 99%
“…Whole body segmentation has been lost, complete with all segmented organ systems, several times within one phylum, namely, the annelids. (41,42) Two unsegmented groups, the sipunculids and the echiurans, previously regarded as phylum level taxa, have now been shown to be nested within polychaete annelids. (43) Both taxa retain transient vestiges of a segmented body plan during their development.…”
Section: The Case Against a Common Origin Of Segmentationmentioning
confidence: 99%
“…It is suggested that cladistic analyses using morphological data may fail to recognise absent characters as losses rather than as primary absences Bleidorn, 2007;see Fitzhugh, 2008). Thus, the sister-group relationship Polychaeta-Clitellata as found in Rouse and Fauchald (1997) may have been biased by the misinterpretation of a number of convergently lost characters.…”
Section: Annelid Systematicsmentioning
confidence: 99%
“…Such loss of characters is clearly a plausible and common phenomenon (e.g. Jenner 2004;Bleidorn 2007). At present we tend to then fall back on supposing that this rare retention of ancestral complexity can be revealed by the same complex genetic network being used in such supposed non-derived lineages.…”
Section: (Aguinaldo Etmentioning
confidence: 90%
“…The discussions on the reconstruction of the annelid and clitellate ancestors have been reviewed in greater detail elsewhere (e.g. Bartolomaeus et al, 2005;Bleidorn, 2007;Nielsen, 2001;Purschke, 2002;Rouse & Fauchald, 1997;Rouse & Pleijel, 2001;Westheide, 1997;Westheide et al, 1999). There is still plenty of debate about the form of these ancestors in addition to the processes outlined above.…”
Section: The Annelid Ancestormentioning
confidence: 99%
See 1 more Smart Citation